The eye pressure dynamics during glaucomatous shunt surgery with uveoscleral outflow activation - S. A. Volik; A. Kh. Kade; E. I. Volik (Кубанский научный медицинский вестник, 2015)
The studies of influence all the phases of uveoscleral outflow stimulation on the intraocular pressure (IOP) level were carried out in the course of 37 glaucomatous operation. Two methodics of glaucomatous surgery and two viscoelastics with different pseudoplasticity were compared. The IOP measurement was carried out intraoperatively and 24 hours later. It was stated that posterior sclerectomy was accompanied by IOP decrease on 4,0±0,5 mm Hg (p